ANALISIS PENGARUH VARIASI TEMPERATUR PEMBAKARAN MOLASE TERHADAP VOLUME DAN KADAR BIOETANOL YANG DIHASILKAN DENGAN PROSES PIROLISIS - Dimas Yoga Arianto; Basuki Basuki; Dian Anisa Rokhmah Wati; Mohammad Munib Rosadi (JURNAL ILMIAH NUSANTARA, 2024)
The purpose of this research is to produce liquid volume and bioetanol content of the pyrolysis process. The results of this study are in the form of test results from pyrolysis. The test results at 70 ℃ produced a pyrolysis liquid volume of 726.6 ml, at 80 ℃ produced a pyrolysis liquid volume of 886.6 ml. At 90 ℃ produces a liquid volume of 1,190 ml. While at 70 ℃ produces bioetanol content with a percentage of 30.3 %, 80 ℃ produces bioetanol content with a percentage of 47 %, 90 ℃ produces bioetanol content with a percentage of 21.3 %. Both research results can be seen in the results of the Kruskal Wallis test which states the same sig value of 0.025 <0.05.